Improvement of energy density and energy yield of oil palm biomass by torrefaction in combustion gas - masaharu, komiyama (2018)

(untitled)
his study investigates torrefaction of oil palm empty fruit bunch (EFB) and palm kernel shell (PKS) in a fixed-bed reactor in biomass combustion gas, which consisted of 8-9 vol% O2 and 13-14 vol% CO2. Torrefaction experiments were carried out at 473-573K for 30 min. The mass and energy yields, and properties of torrefied biomass were investigated. Torrefaction in the presence of combustion gas resulted in a decrease in mass yield and an increase in the energy density and carbon content. For both the biomass, the highest energy yield and density was obtained by torrefaction at 473 K and 573 K in combustion gas, respectively. This study has proved that use of combustion gas has advantages in terms of product yield as well as energy saving. Production capacity of torrefied biomass at oil mill was also estimated. © Published under licence by IOP Publishing Ltd.